(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
In life, we walk alongside people who leave their mark on us in the form of a trail. In a way they become inner voices that accompany us when we reflect, that is to say, in a certain way we follow their course. This is the case I experienced with Juan Francisco Sans Moreira. I was struck by his knowledge and the endless activities he carried out, but also by the nobility contained in his being. Mariantonia Palacios was always by his side. Picasso, in his paintings, made two faces into one. Just like them.